Relationship Between Biometric Factor of the Host and Giant Piper's Growth (Piper decumanum L.) in the Education Forest of Papua University, Manokwari - Elieser V. Sirami; Devi Manuhua (JURNAL KEHUTANAN PAPUASIA, 2022)
The biometric factors of the host, soil properties, microclimate, and biologic components are influencing the growth of climber Piper species. However, ecological data is rarely available in scientific journals. This research aims to determine the relationship between host plant biometric factors and P. decumanum growth in the University of Papua Manokwari education forest. The data were acquired using the systematic line method, with the hypothetical plot and sampling tree as the center of the plot. The relationship between the host's biometric factor and the growth of P. decumanum is evaluated using partial correlation analysis. Stands with a large DBH, high density, and rough bark texture are preferred by P. decumanum. The number of individuals and the total height of P. decumanum increased with DBH, crown area, branch-free height, total height, crown height, skin texture, and affected shade area. The number of individuals was limited by total height, branch-free height, crown height, skin texture, and crown area. On the other hand, the shaded area prevented P. decumanum from growing taller. P. decumanum most probably requires a large vertical growing space to share with the same species and other climbing species, possibly requiring support to reach the maximum height of the forest canopy. The adhesive root's ability to cling is influenced by the roughness of the host bark, and a broad shade is required to control the microclimate factors.